Kosmologi Koda Kirin dan Ekoteologi Lamaholot - Daya Negri Wijaya; Muhammad 'Afwan Mufti (Universitas Hamzanwadi, 2026)
The ecological crisis in Indonesia is driven not only by the exploitation of natural resources but also by an anthropocentric worldview that separates humans from nature. In this context, the Koda Kirin cosmology of the Lamaholot people introduces the concept of Rera-wulan Tana-ekan, which views the sky, the earth, and humanity as a single relational unity. This study aims to analyze the Koda Kirin cosmology and the teachings on nature conservation passed down through oral traditions and customary practices of the Lamaholot community as the foundation of local eco-theology. The research employs a qualitative method with an ethnohistorical approach—that is, an ethnic historical study that reconstructs past social events through both social facts (sociographic) and mental facts (mentifacts) of the community. Data were collected through in-depth interviews, participant observation, focus group discussions (FGDs), and literature review. Oral traditions, customary narratives, and customary practices were analyzed as mental facts and social facts representing collective memory. The research process began with the identification of key informants, field data collection, thematic analysis, and culminated in interpretive writing. This study aims to examine a model of nature conservation based on the traditional beliefs of the Lamaholot people. The results indicate that Rera-wulan Tana-ekan serves as the cosmological center of Lamaholot society, governing human relationships with the land, forests, and water through rituals, taboos, and communal mechanisms. They view environmental degradation as a violation against their ancestors that carries both ecological and social consequences. These findings confirm that Lamaholot eco-theology is a values-based conservation model that grows from collective consciousness and is relevant to sustainable development based on local wisdom. Furthermore, this study also contributes a novel perspective to nature conservation amidst the phenomenon of the ecological crisis.